La Evaluación Ambiental Estratégica (EAE) en Colombia: su adopción, criterios para la estructuración de su procedimiento administrativo y su aplicación a los planes de ordenamiento territorial - Gómez, Jorge (Revista Científica, 2011)
The purpose of this research was to propose formal models of political administrative procedure for the strategic environmental assessment (SEA) in Colombia, which applies at the level of policies, plans and programs (PPP). From the debate on the theoretical principles of the environmental assessment and from the Colombian experience with the Environmental Impact Assessment -EIA (complemented with the short history of the SEA), it is possible to obtain from there criteria to sructurise the different steps of the administrative arrangement and process of the SEA. From these principles it is possible to derivate various models for the SEA, considering basically two of them: One that is similar to the classical EIA, that presumes to follow in a similar fashion the order of succession of steps of the procedure of the EIA as applied in Colombia (that implies at least having a draft of the design of the PPP, in order to make it go through the environmental assessment and from its results obtain the measures and recommendations that are to be considered) and, another one based on the integration of the SEA accompanied by the planning and design process of the PPP and simultaneously introducing in them the pertinent changes from the environmental perspective. In the particular field of spatial planning in Colombia and according to existing procedure or arrangement and its determinant key points for the planning and formal agreement of the Territorial Organisation Plans the most adequate model to be applied would be the second referenced one, in other words, the integrated SEA, in which there is the simultaneous articulation among the phases of the SEA with the steps of the planning (design) of the Territorial Organisation Plan.